EFFECT OF BATTER METHOD AND PROOFING TIME ON PHYSICAL AND SENSORY CHARACTERISTICS OF GLUTEN-FREE BREAD - Imro’ah Ikarini; Aji Sutrisno; Sudarminto Setyo Yuwono (Jurnal Teknologi Pertanian, 2022)
Indonesia's dependence on wheat imports can be reduced by looking for alternatives to local flour-based preparations. Bread products currently depend on raw materials in the form of wheat flour. In addition to availability problems, the gluten content in wheat flour also causes allergies in people with celiac disease. Celiac sufferers should consume gluten-free bread. As alternatives, flour derived from cereals and tubers, such as rice, corn, potato, and cassava, can be used in bread processing. The absence of gluten from the bread composition results in pale, less fluffy bread and firm crumbs; therefore, it is necessary to modify the batter to improve gluten-free bread quality. This study aims to analyze the effect of straight batter and no time batter methods, also the proofing time of 45 and 60 minutes on the bread-specific volume, firmness, crumb and crust colour, and panelist response. This study used a Completely Randomized Design with two factors. The result of the study shows that the batter method and proofing time significantly affected the bread-specific volume, firmness, and sensory acceptance but had no significant effect on crust colour and crumb. The overall sensory analysis found that the bread made using the straight batter method with 45 minutes of proofing time was the most preferred among the panelists